APPLICATION OF COMPUTER TECHNOLOGIES IN MEDICINE - Elmurotova Dilnoza Baxtiyorovna; Yoqubboyeva E’zoza Zokirjon qizi; Orifqulova Malika Fazliddin qizi; Imanova Laura Nurmaxan qizi (Western European Studies, 2024)
At present, computers have become widespread in many branches of medicine. The work shows the chronological scale of the relationship between computer technologies and medicine from 1954 to 2006. The advantages and disadvantages of EMR and CDSS are shown.
Keywords: EMR; CDSS; NVMe drive; history